Airway Management in Complete Oral Cavity Foreign Body Obstruction: A Case Report. Issue 1 (19th January 2021) - Jimenez-Ruiz, Federico; Van Beck, Jenna; Jakubowski, Luke; Kim, Tae
Abstract : Foreign body (FB) injuries of the airway and of the digestive tract are common in pediatric patients. Available literature cites small blunt objects as a common FB leading to FB aspiration or ingestion. Complete oral cavity obstruction by a FB, however, is a rare and potentially life-threatening scenario. Airway management can be particularly challenging when access to the oral cavity is severely restricted. We present the anesthetic management of a child with complete oral cavity obstruction by a large fishing lure.